Accumulation of Pb in Chinese cabbage (Brassica rapa) and bean (Phaseolus vulgaris) from the use of fertilizer and pesticide - Yekti Sri Rahayu; Tatik Wardiyati; Moch Dawam Maghfoer (Journal of Degraded and Mining Lands Management, 2020)
A series of experiments in a plastic house were carried out to test the accumulation of Pb metal in Chinese cabbage and bean plants from the application of several Pb sources. The research method used was a split-plot design with the main plot was the application of Pb source consisting of A1 = pesticide (99 mg Pb/kg), A2 = fertilizer (21 mg Pb/kg), A3 = Pb(NO3)2 (50 mg Pb/kg) and A4 = control (without the application of Pb), and the subplot was the vegetable crops consisting of B1 = Chinese cabbage (Brassica rapa) and B2 = bean (Phaseolus vulgaris). The results of the experiment showed that the Pb content in the shoots of Chinese cabbage and bean plants that were previously sprayed with pesticide was significantly 231.02% (Chinese cabbage) and 257.18% (bean) higher than control plants. Meanwhile, the largest Pb concentrations in the roots of Chinese cabbage and bean plants were obtained in plants applied with Pb(NO3)2. Compared to the control treatment, there was an increase in Pb concentration by 206.32% in the roots of Chinese cabbage plant and by 310.03% in the roots of bean plant which were applied with Pb(NO3)2. Pb concentrations of Chinese cabbage which were given fertilizer increased by 14.86% in the shoot and 30.59% in the root, while those in bean increased by 10.74% in the shoot and 98.77% in the root. Pb concentrations in Chinese cabbage and beans that were given fertilizer were not significantly different from control plants. These results indicate that the application of pesticide and fertilizer containing Pb results in Pb accumulation in the plant shoots and roots as well as in the soil.